PENGUKURAN KINERJA APARTEMEN SEBAGAI TEMPAT TINGGAL MAHASISWA Analisis Kepuasan Pengguna di Kawasan Edutown, Jatinangor, Indonesia - Asep Yudi Permana (Jurnal Arsitektur ZONASI, 2022)
Abstract, The development of educational areas in Indonesia is not followed and prepared with policies that accommodate adequate infrastructure, so that the existence of rental housing facilities such as boarding houses, rented houses is increasingly mushrooming, all of which are left to the community around the campus. The phenomenon of apartments as student residences is increasingly stretched along with the increasing level of economy and lifestyle. The purpose of the study was to assess the level of student satisfaction with accommodation facilities. The study adopted a literature review related to the level of student satisfaction with apartment facilities using a questionnaire instrument. A total of 90 students who live in Easton, Pinewood, and Skyland apartments become research respondents. The data collected were analyzed using the average score, chi-square test (χ2), and space syntax analysis. The results revealed a total average satisfaction level of 3.55 (on a 5-point Likert scale), which indicates that students are satisfied with apartment accommodation facilities. The indicators of privacy, security, and accessibility are indicators that show the highest level of satisfaction compared to the other 12 indicators. Further research shows that age, marital status, and regional origin have a significant effect on overall student satisfaction with accommodation facilities provided by apartment managers. The implication is that this study provides valuable feedback for developers/investors in determining the type of apartment room that students are interested in as a residence in the edutown area, it also helps universities in developing and providing dormitories and facilities according to student needs. The indicators in this study have been tested significantly in assessing the level of student satisfaction about apartment accommodation facilities and can be used to assess user satisfaction with similar facilities in other locations or countries. Keywords: Education Area, Infrastructure, Phenomenon, Accommodation, Space syntax analysis Abstrak, Perkembangan kawasan pendidikan di Indonesia tidak diikuti dan dipersiapkan dengan kebijakan yang mengakomodasi infrastruksi yang memadai, sehingga keberadaan fasilitas hunian sewa seperti kost, rumah kotrakan semakin menjamur yang semua pemenuhannya diserahkan kepada masyarakat sekitar kampus. Phenomena apartemen sebagai hunian mahasiswa semakin menggeliat seiring semakin meningkatnya tingkat ekonomi dan gaya hidup. Tujuan penelitian adalah untuk menilai tingkat kepuasan mahasiswa terhadap fasilitas akomodasi. Penelitian mengadopsi tinjauan pustaka terkait dengan tingkat kepuasan mahasiswa terhadap fasilitas apartemen dengan menggunakan instrument kuesioner. Sebanyak 90 mahasiswa yang tinggal di Easton, Pinewood, dan Skyland apartment menjadi responden penelitian. Data yang terkumpul dianalisis menggunakan skor rat-rata, uji chi-kuadrat (χ2), dan space syntax analysis.  Hasil, mengungkapkan adanya tingkat kepuasan rat-rata total 3,55 (pada skala likert 5 poin), yang menunjukkan bahwa mahasiswa puas dengan fasilitas akomodasi apartemen. Indikator privasi, keamanan, dan aksesibilitas menjadi indikator yang menunjukkan tingkat kepuasan yang paling tinggi dibandingkan dengan 12 indikator lainnya. Penelitian lebih lanjut menunjukkan bahwa usia, status pernikahan, dan asal daerah berpengaruh siginfikan terhadap kepuasan mahasiswa secara keseluruhan terhadap fasilitas akomodasi yang disediakan pengelola apartemen. Implikasi, studi ini memberikan upman balik yang berharga bagi pengembang/investor dalam menentukan tipe kamar apartemen yang diminati mahasiswa sebagai hunian di kawasan edutown, juga membantu bagi perguruan tinggi dalam pengembangan dan penyediaan asrama dan fasilitasnya sesuai kebutuhan mahasiswa. Indikator dalam penelitian ini sudah diuji secara signifikan dalam menilai tingkat kepuasan mahasiswa tentang fasilitas akomodasi apartemen dapat digunakan untuk menilai kepuasan pengguna dengan fasilitas serupa di lokasi atau negara lain. Keywords:  Kawasan Pendidikan, Infrastruktur, Fenomena, Akomodasi, Space syntax anaysis.